Gasification of biomass model compounds in supercritical water: Detailed reaction pathways and mechanisms. (29th August 2022) - Wang, Cui; Zhu, Chao; Huang, Jianbing; Jin, Hui; Lian, Xiaoyan
Abstract: Supercritical water gasification (SCWG) technology is an efficient and clean method to utilize biomass wastes. But the real biomass is complicated, bringing difficulties for the research of reaction pathway. In this paper, xylose was selected as a model compound for hemicellulose and the experiment was conducted in quartz reactors. The degradation pathway of xylose in supercritical water (SCW) was discussed. The main intermediates included phenols, furans, arenes, organic acids, ketones and alcohols. Phenols and arenes were difficult to be gasified while furans, organic acids, ketones and alcohols could be easily gasified. The degradation pathways of glucose and guaiacol as model compounds for cellulose and lignin in SCW have also been discussed in previous studies. By comparing the experimental data, it is found that guaiacol was more difficult to be gasified than glucose and xylose. The main organics in residual liquid of xylose and glucose were furans, cyclic ketones, open-chain compounds, phenols and arenes while that of guaiacol were phenols, arenes and open-chain compounds. The degradation of phenols and arenes was the key step of SCWG of biomass model compounds. Graphical abstract: Image 1 Highlights: Degradation pathway of xylose in SCW was proposed. Gasification processes of xylose, glucose and guaiacol in SCW were compared. Key step to increase CGE and HGE of biomass model compounds was raised.